Chironomidae of Central America - Hamerlík, Ladislav, author.
1 online resource
Keywords: This illustrated introduction to Central American Chironomidae offers extensive photographic material, as well as detailed morphological and ecological descriptions of chironomid subfossils found in Central American lake sediments. The book uniquely provides two identification keys: one for living larvae occurring (or potentially being present) in Central America and one for the recorded subfossil remains, using limited morphological characters. Paleolimnological investigations using chironomid remains have undergone a resurgence of interest, and this taxonomic guide will aid the thorough analysis of the diversity and distribution of the taxa encountered to date in Central America. Out of the total 64 described genera, the book brings 20 endemic genera, and more than half of the presented morphotypes are new. Plates are included for each taxon with generic characters and also provide a key to morphotypes, if present, their specific characters, distribution, and ecology. Authored by a (paleo)limnologist and a taxonomist, the guide draws on a thorough taxonomical knowledge of the region's recent chironomid fauna. It uses a paleolimnological approach to transmit this information to morphotypes that can be linked with ecology and used to reconstruct the past development of nature. The book thus helps paleo-workers and taxonomists to learn more about these fascinating insects and, through them, to discover the world around us. Providing a comprehensive reference for aquatic ecologists, paleolimnologists, students, and researchers, the guide will also be of interest to non-academic professionals working on applied research and biomonitoring of lakes. It will be useful for people studying both recent and subfossil material, not only in Central America, but in the whole Neotropical region.